IMPLEMENTASI AUGMENTED REALITY BERBASIS FILTER INSTAGRAM PADA PENERAPAN MEDIA PEMBELAJARAN TENTANG PENGENALAN TATA SURYA - Dhimas Adi Satria; Rokhmatullah B. Firmansyah; Aditya Akbarsyah Basuki (JURNAL ILMIAH INFORMATIKA, 2023)
The need for interactive media in learning is starting to be in demand by the wider community and along with the increasing use of Smartphones in times like this Augmented Reality (AR) is a new medium in the learning process of children's Natural Sciences in recognizing the planets in the Solar System and can handle problems from traditional learning media that exist today which are felt to be less informative and interactive for children, from the function of using educational media that can visualize various objects and information that can arouse curiosity in students so that children can start to be more active in learning. With Augmented Reality (AR) technology, it aims to make children able to directly visualize their child's imagination about the planets. This interactive 3D multimedia learning media using Instagram-based Augmented Reality technology was created with Blender 3D Software 2.93, Spark AR Studio 141 The results of this study are the application of Augmented Reality learning media for solar system based on Instagram filters